2008
DOI: 10.3389/neuro.03.002.2008
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated H-Current in hyperexcitable CA1 dendrites after febrile seizures

Abstract: Somatic recordings from CA1 pyramidal cells indicated a persistent upregulation of the h-current (I h ) after experimental febrile seizures.Here, we examined febrile seizure-induced long-term changes in I h and neuronal excitability in CA1 dendrites. Cell-attached recordings showed that dendritic I h was signifi cantly upregulated, with a depolarized half-activation potential and increased maximal current. Although enhanced I h is typically thought to be associated with decreased dendritic excitability, whole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 39 publications
(86 reference statements)
3
59
0
Order By: Relevance
“…However, the role of HCN disorders in epilepsy is complex. Studies in experimental models indicate that both up-regulation (Dyhrfjeld-Johnsen et al, 2008;Gill et al, 2006) and down-regulation (Powell et al, 2008;Richichi et al, 2008;Santoro et al, 2010;Shah et al, 2004;Strauss et al, 2004) of HCN channels can be associated with seizures. Our Q5 data were clearly inconsistent with an increase in I h current during the neuronal hyperexcitability in CA1 region of the hippocampus.…”
Section: Q3mentioning
confidence: 98%
“…However, the role of HCN disorders in epilepsy is complex. Studies in experimental models indicate that both up-regulation (Dyhrfjeld-Johnsen et al, 2008;Gill et al, 2006) and down-regulation (Powell et al, 2008;Richichi et al, 2008;Santoro et al, 2010;Shah et al, 2004;Strauss et al, 2004) of HCN channels can be associated with seizures. Our Q5 data were clearly inconsistent with an increase in I h current during the neuronal hyperexcitability in CA1 region of the hippocampus.…”
Section: Q3mentioning
confidence: 98%
“…Of particular interest is the contribution of these different effects as neuronal excitability is probed when membrane potentials are held at common levels. Holding membrane potentials at common hyperpolarized levels has been suggested as a way to compensate for changes in resting membrane potentials with I h up-regulation (Rosenkranz and Johnston 2006;Dyhrfjeld-Johnsen et al 2008). Our modeling results suggest that, although holding potentials at common levels can bring modulated neurons to within equal voltage differences from their voltage firing thresholds, this protocol may exaggerate the excitability-depressing shunting effect caused by changes in input resistances with I h up-regulation.…”
Section: Introductionmentioning
confidence: 43%
“…Another possible limitation of our simple compartmental models is that they do not accurately capture the spatial distribution of h channels or neuron morphology that may be influencing the effects of I h up-regulation. This possibility is supported by computational modeling results reported by Dyhrfjeld-Johnsen et al (2008) in their investigation of up-regulation of I h in dendrites of hippocampal pyramidal cells following febrile seizures. They compared the excitability of three different, multi-compartmental, morphologically accurate CA1 pyramidal neuron models when up-regulation of dendritic I h was simulated in a manner suggested by their experimental recordings.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Importantly, in pyramidal cells from eFS rats, a short train of inhibitory postsynaptic potentials (IPSPs) (6 IPSPs at 50 Hz), which resembled those that occur spontaneously during the θ rhythm in vivo, but not single IPSPs, triggered post-inhibitory rebound depolarization and firing, phenomena abolished by the selective HCN blocker ZD-7288. Recently, from both whole-cell dendritic recordings and computer models of CA1 pyramidal cells, Dyhrfjeld-Johnsen et al have further confirmed the upregulation of dendritic I h in eFS rats leading to persistent dendritic hyperexcitability, primarily due to increased I h -induced depolarization of the resting membrane potential (84). Thus, it is likely that the conjunction of the potentiation of inhibitory inputs and the frequency-dependent modified I h -mediated events generated persistent hyperexcitable foci in the hippocampus following FS.…”
Section: Do Efs Induce Neurophysiological Changes?mentioning
confidence: 89%